THE SUCCESS FACTORS OF TEAM SPORTS FOR UNIVERSITY ATHLETE OF THAILAND - Cruthka, Pornvijak; Sangpook, Natchanon (Journal of MCU Nakhondhat, 2024)
The objectives of this research were to 1) Study the concerning personal motivation; physical fitness; mental fitness; the athletes potential and skills; policy and supporting; sports team of coaches and sponsorship; and sports facilities. Furthermore, the researchers study 2) The factor analysis of the success factors of team sports for University athlete of Thailand. This is survey research, and used to conceptual framework of the success factors of team sports. The sample was 401 athletes of University. The instrument used for data collection was questionnaire. Testing for quality, the researchers found that the instruments evinced reliability at the levels of 0.97. The researchers analyzed the data collected in terms of frequency, percentage, mean and standard deviation. In addition, the exploratory factor analysis by orthogonal rotation with varimax method was used to extract factors. The researchers found that 1) Athletes of University exhibited levels of opinions regarding personal motivation at a highest level and in three aspects at a high level in the following descending order of means: sports team of coaches and sponsorship; policy and supporting; and sports facilities. Furthermore, the opinions concerning behavior to practicum regarding mental fitness; the athletes potential and skills and physical fitness at a level often. 2) There were the success factors of team sports for University athlete of Thailand ten components, described by 72 variables. Loading factors ranged from .405 to .830. They were explanatory of variance at 62.77 percent. The name of components were as follows: 1) Sports team of coaches; 2) Sports facilities; 3) Physical fitness; 4) The athletes potential and skills; 5) Policy and supporting; 6) Mental fitness; 7) Stress management; 8) Personal intrinsic motivation; 9) Personal extrinsic motivation; and 10) Sport potential development.